G379(P) Acute bacterial meningitis in children before nd after pneumococcal vaccinein pakistan national immunisation program; a comparison. (24th May 2017) - Bari, A; Zeeshan, F; Zafar, A; Ejaz, H; Rathore, A Waheed
Abstract : Objective: To describe disease pattern, bacteriological profile, morbidity and mortality of acute bacterial meningitis (ABM) in children and to compare these parameters before and after the introduction of Pneumococcal vaccine in Pakistan National Immunisation Program. Study design: A descriptive study. Methodology: A total of 503 children 1 months to 5 years of age admitted with diagnosis of meningitis. Complete blood count, CSF cytology, biochemistry, culture sensitivity and blood culture sensitivity were performed. Data was analysed using SPSS 20. Results: Out of 503 children with ABM, there were 199 cases in 2012 and 304 in 2013–2015. Frequency of meningitis decreased by 50%.Most children in both groups were under one year. Relatively less children were fully vaccinated in new group, 30.3% vs 45%.Increased complications seen in the newer group 20% vs 17%.CSF culture positivity decreased from (12%) to (6.6%). The common pathogens identified on CSF culture were Coagulase negative staphylococci (CoNS) 11 (5.5%), Streptococcus pneumoniae 5 (2.5%), H. influenzae 2 (1%) in 2012, whereas in the new group Klebsiella 7 (2.3%) was the most common followed by Streptococcus pneumoniae 4 (1.3%), and (CoNS) 3 (1%). Refusal to take feed (p=0.002), impaired sensorium (p=<0.001), severe malnutrition (p=0.001), prolonged duration of symptoms (p=<0.001)and incomplete vaccination status (0.005)were associated with mortality. Mortality rate decreased from 20 (10%) in 2012 to 17 (5.6%) in 2013–2015 but more children developed neurological squealier 2.7% versus 1% previously. Conclusion: Acute bacterial meningitis mostly affected children<1 year. Frequency and mortality of meningitis decreased significantly but more severe disease with neurological complications developed in those children who were unvaccinated in 2013– 2015 compared with 2012.